Optimized Ensiling Conditions and Microbial Community in Mulberry Leaves Silage With Inoculants - Cui, Xiaopeng; Yang, Yuxin; Zhang, Minjuan; Jiao, Feng; Gan, Tiantian; Lin, Ziwei; Huang, Yanzhen; Wang, Hexin; Liu, Shuang; Bao, Lijun; Su, Chao; Qian, Yonghua (Frontiers in Microbiology, 2022)
Mulberry leaves (ML) are a promising alternative fodder source due to their high protein content and the abundance of active components. A test of three inoculants in various combinations revealed that high-quality ML silage was produced at an inoculum ratio of 1:1:0 (50% Saccharomyces cerevisiae, 50% Lactobacillus plantarum, and 0% Bacillus subtilis). Using dry matter (DM) loss, pH, ammonia-N and amino acid contents, total antioxidant activity, and total flavonoids content to evaluate silage quality, this inoculant mixture was shown to produce high-quality silage within a range of inoculum size (5–15%), moisture contents (50–67%), ensiling temperatures (27–30°C), and ensiling duration (14–30 days). A third trial comparing silages produced after 30 days at 28°C and 50% moisture content revealed that silage E, prepared using an L. plantarum inoculant alone, displayed the lowest DM loss and pH, and low bacterial diversity, and it was dominated by Lactobacillus (88.6%), with low abundance of Enterobacter (6.17%). In contrast, silage B5, prepared with equal ratios of L. plantarum and S. cerevisiae, was dominated by Enterococcus (67.16%) and Lactobacillus (26.94%), with less marked yeast persistence, and reducing the DM content from 50 to 40% altered these relative abundances to 5.47 and 60.61, respectively. Control silages produced without an inoculant had the highest pH and ammonia-N content (indicative of poor quality), had the lowest antioxidant activity, had higher bacterial diversity, and were dominated by Carnobacterium (74.28%) and Enterococcus (17.3%). In summary, ensiling of ML conditions with proper inoculants yielded high-quality silage with a favorable microbial community composition.